2022
DOI: 10.21203/rs.3.rs-2094231/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Review of Interventions to promote HPV Vaccination Globally

Abstract: Background Despite the human papillomavirus (HPV) vaccine being a safe, effective cancer prevention method, its uptake is subomptimal in the United States (U.S.). Previous research have found a variety of intervention strategies (environmental and behavioral) in increasing its uptake. The purpose of the study is to systematically review the literature for interventions to promote HPV vaccination from 2015 to 2020. Methods We updated a systemative review of interventions to promote HPV vaccine uptake globall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
(280 reference statements)
0
1
0
Order By: Relevance
“…One review evaluating interventions to promote HPV vaccination globally found that only 25% of interventions conducted between 2015 and 2020 focused on young adults aged 18–34 years. 12 One of the challenges faced in this current work is that many reviews include a wide age range of participants when they include young adults. Two reviews investigating the effectiveness of HPV interventions targeted adolescents to young adults aged 9–26 years.…”
Section: Introductionmentioning
confidence: 99%
“…One review evaluating interventions to promote HPV vaccination globally found that only 25% of interventions conducted between 2015 and 2020 focused on young adults aged 18–34 years. 12 One of the challenges faced in this current work is that many reviews include a wide age range of participants when they include young adults. Two reviews investigating the effectiveness of HPV interventions targeted adolescents to young adults aged 9–26 years.…”
Section: Introductionmentioning
confidence: 99%